Analisa Kajian Penggunaan Alat Berat Pada Pekerjaan Tanah Proyek Pembangunan Jalan (Studi Kasus : Zona I Pada Proyek Pembangunan Jalan Tol Padang-Pekanbaru By Pass Km 25) - Jajang Atmaja (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
A project work rarely runs smoothly, usually there will be some obstacles. Excavation, stockpiling, and compaction work is an early stage of road construction that requires heavy equipment assistance. One of the causes of problems that usually arise in earthworks using heavy equipment is in the form of an operator who is not skilled. This study aims to calculate the productivity, cost and time of heavy equipment and calculate the composition of heavy equipment usage. The method used in this study was to collect primary and secondary data. The results of the calculated analysis show that the most efficient composition is in the third alternative, namely 2 Excavators 676.04 m³ / day, 5 Dump Trucks 260.75 m³ / day, 2 Bulldozers; 807.93 m³ / day, 2 SheepFoot Rollers; 1215.90 m³ / day, 2 Vibration Rollers; 1215.90 m³ / day, and 3 Water Tanker Trucks; 479.99 m³ / day with a total cost of IDR 2,131,752,569.29